Geomorphological characteristics of the Southwest waters of Vietnam - Le, Dinh Nam; Vu, Van Phai; Do, Huy Cuong; Tran, Anh Tuan; Duong, Quoc Hung; Phan, Dong Pha; Vu, Le Phuong; Tran, Xuan Loi; Tran, Hoang Yen (Vietnam Journal of Marine Science and Technology, 2022)
Based on the principle of origin, the Southwestern coastal topography of Vietnam is divided into 32 geomorphological units. Coastal and island topography consists of 9 geomorphological units belonging to 4 topographic groups: (i) terrain with the common erosive origin, (ii) plants of marine origin, (iii) mixed river and sea origin, and (iv) waste of biological origin - river and sea. The seabed topography consists of 23 geomorphological units belonging to 3 topographic groups (i) topography of marine origin; (ii) economics of river and sea origin; (iii) marsh-sea accumulation terrain. The topography of a small part of the coastal continent and most islands were formed in the Quaternary period, and the rest of the continental coastal topography and the entire seabed surface of Southwest Vietnam was developed in the Quaternary period, from late Pleistocene to Holocene.